The Effects of Anxiety, Stress, and Depression Due to Covid-19 Pandemic on Sleep Quality of Workers in Hospital (Media Kesehatan Masyarakat Indonesia, 2021)
The cases of COVID-19 infection have increased quite rapidly in Indonesia. The COVID-19 pandemic situation makes people experience anxiety, stress, and depression, especially those who work in hospitals. It further affects their sleep quality. The purpose of this study was to determine the effects of anxiety, stress, and depression due to the COVID-19 pandemic on the sleep quality of healthcare and non-healthcare workers in a type-D hospital in Yogyakarta. This research was an analytic observational study with a cross-sectional design. The subjects of this study were 200 healthcare and non-healthcare workers who worked in type-D hospital in Yogyakarta. This research applied DASS-42 questionnaire to measure the stress levels. While for measuring the sleep quality, it used PSQI questionnaire. Furthermore, to determine the effects of anxiety, stress, and depression on sleep quality, the researchers used a Chi-Square statistical analysis with a 95% confidence level. The result indicated that anxiety and stress affected the sleep quality of health workers (p=0.009; p=0.026), while anxiety and depression affected the sleep quality of non-helath workers (p=0.025; p=0.019). Conditions of anxiety, stress, and depression are more at risk of having bad sleep quality than who don’t experience it (Health workers OR value = 4.313; 5.053; 3.122, Non-health workers OR value = 4.876; 4.533; 0.551).
Keywords: Covid-19; anxiety; depression; sleep quality; stress